The straight and isolated G350.54+0.69 filament: density profile and star formation content. Issue 2 (13th June 2018) - Liu, Hong-Li; Stutz, Amelia; Yuan, Jing-Hua
ABSTRACT: We investigate the global properties of the straight and isolated filamentary cloud G350.54+0.69 using the Herschel continuum and APEX molecular line data. The overall straight morphology is similar to that of two other well-studied nearby filaments (Musca and Taurus-B211/3), while the isolated nature of G350.54+0.69 appears similar to that of Musca. G350.54+0.69 is composed of two distinct filaments, with a length ∼5.9 pc for G350.5-N (∼2.3 pc for G350.5-S), a total mass of ∼810 M⊙ (∼110 M⊙ ), and a mean temperature of ∼18.2 K (∼17.7 K). We identify nine dense and gravitationally bound cores in the whole cloud G350.54+0.69. The separations between cores and the line mass of the whole cloud appear to follow the predictions of the 'sausage' instability theory, which suggests that G350.54+0.69 could have undergone radial collapse and fragmentation. The presence of young protostars is consistent with this hypothesis. The line masses of the two filaments (∼120 M⊙ pc −1 for G350.5-N and ∼45 M⊙ pc −1 for G350.5-S), the mass–size distributions of the dense cores, and the low-mass protostars collectively suggest that G350.54+0.69 is a site of ongoing low-mass star formation. Based on the above evidence, we place G350.54+0.69 in an intermediate evolutionary stage between Musca and Taurus-B211/3. We suggest that investigations into straight (and isolated) versus those distributed inside molecular clouds may provide important clues into filament formation and evolution.